2009
DOI: 10.1177/1545968309348508
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Turning 180° During the Timed Up and Go in Stroke Survivors With and Without Falls History

Abstract: These results indicate incidences of falls during turning following stroke may not be due to impaired movement patterns but due to the many other factors that are associated with falls, such as deficits in cognitive processes--attention or central integration--and/or sensory deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 42 publications
6
71
3
Order By: Relevance
“…However, our results show few differences in stepping patterns according to turn direction; a finding that has also been reported in previous studies [5][6][7]. Given that the direction and extent of step asymmetry has been shown to vary according to age, motor recovery level and walking speed [26][27][28], systematic differences in stepping patterns according to the direction of the turn may be obscured by the complexity of relationships between these variables.…”
Section: Discussioncontrasting
confidence: 32%
See 2 more Smart Citations
“…However, our results show few differences in stepping patterns according to turn direction; a finding that has also been reported in previous studies [5][6][7]. Given that the direction and extent of step asymmetry has been shown to vary according to age, motor recovery level and walking speed [26][27][28], systematic differences in stepping patterns according to the direction of the turn may be obscured by the complexity of relationships between these variables.…”
Section: Discussioncontrasting
confidence: 32%
“…Those that have, [5][6][7] showed that apart from delayed initiation of turns, longer time to turn and more steps, overall movement patterns were relatively unaffected, even in participants with a history of falls [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6]), turning (e.g. [7][8][9]) and in initiating and executing step adjustments (particularly to place the foot medially) in response to external cues [10,11]. However, the relationships between poor gait adaptability and functional recovery/mobility are still largely unknown.…”
mentioning
confidence: 99%
“…Multiple steps were used as a turning strategy to increase both stability and balance during the turn. Stroke survivors do not use pivot strategy during 180̊ turn because they move in an "en bloc" pattern, which the body turns into one block in one direction (Hollands et al, 2010). The "en bloc" occurs as one block of body with their neck and trunk rigid, involving in multiple small steps to accomplish a turn rather than the usual twisting of the neck, trunk and pivoting on the toes (Verheyden, Willems, Ooms, & Nieuwboer, 2007).…”
Section: Discussionmentioning
confidence: 99%